2018
DOI: 10.2196/preprints.10683
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meeting Sexual Partners Through Internet Sites and Smartphone Apps in Australia: National Representative Study (Preprint)

Abstract: Background: Studies have reported on the proportion of the population looking for potential sexual partners online, but few have investigated those who have sex with these partners, arguably a more important target group for health promotion.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…There was a research reported that the Internet provided an important information and unmet need for sexual health education, a range of uses of the Internet including searching for specific facts about HIV or STIs, attempting self-diagnoses of symptoms people might be experiencing, finding health care centers that offered HIV/STIs testing and affordable care, and learning about risk reduction techniques (52). Furthermore, the large national survey from Australia reported that the proportion of the population looking for potential sexual partners using Internet and smartphone apps was increased (53). There was 12.09% (2346/19,398) of their respondents reported ever searching for potential sexual partners on websites and smartphone apps, most common among people aged 16-29 years (53).…”
Section: Reproductive Health Education/informationmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a research reported that the Internet provided an important information and unmet need for sexual health education, a range of uses of the Internet including searching for specific facts about HIV or STIs, attempting self-diagnoses of symptoms people might be experiencing, finding health care centers that offered HIV/STIs testing and affordable care, and learning about risk reduction techniques (52). Furthermore, the large national survey from Australia reported that the proportion of the population looking for potential sexual partners using Internet and smartphone apps was increased (53). There was 12.09% (2346/19,398) of their respondents reported ever searching for potential sexual partners on websites and smartphone apps, most common among people aged 16-29 years (53).…”
Section: Reproductive Health Education/informationmentioning
confidence: 99%
“…Furthermore, the large national survey from Australia reported that the proportion of the population looking for potential sexual partners using Internet and smartphone apps was increased (53). There was 12.09% (2346/19,398) of their respondents reported ever searching for potential sexual partners on websites and smartphone apps, most common among people aged 16-29 years (53).…”
Section: Reproductive Health Education/informationmentioning
confidence: 99%